(untitled) (مجلة البحوث الأكاديمية, 2022)
The aim of this study is to introduce an approach that utilizes a fuzzy logic-based methodology to reduce the impact of uncertainties on the activities of the projects. In this study, the approach presents a method for finding accurate project estimation activities time as compared with the estimation of time of project activities by using the Project Evaluation and Review Technique (PERT). The comparison reveals the proposed method significantly reduced the impact of uncertainties on obtained results to specify the project critical path which led to an improvement in the estimated project completion time.